Kinematical analysis of the men`s long jump at the 2008`s IAAF World Indoor Championships in athletics - Campos, J.; Gamez, J.; Encarnacion, E. (World Congress of Performance Analysis of Sport VIII, 2008)
Performance is dependent not only of speed, but also from technique variables and the ability of the jumper to acquire a good posture in order to create effective forces during the compression phase, which determine the gain in vertical velocity of CG. It was confirmed that the velocity changes are the result of the actions occurring in that phase where takes place the increase of the effective stiffness for resist the impact forces.